Culicidae (diptera: Culicomorpha) from the central brazilian amazon: Nhamundá and abacaxis rivers - Hutchings, Rosa Sá Gomes; Honegger, Roger William Hutchings; Sallum, Maria Anice Mubeb (Zoologia, 2013)
Mosquito fauna (Culicidae) from remote areas along the geographical limits of the State of Amazonas were assessed by employing CDC, Shannon, Malaise and Suspended traps, together with net sweeping and immature collections. Two hundred and six collections were performed in seven localities along the Nhamundá and Abacaxis Rivers, State of Amazonas, Brazil, during May and June 2008. The northernmost locality was 120 km from Nhamundá, whereas the southernmost locality was 150 km from the mouth of the Abacaxis River. The 5,290 mosquitoes collected are distributed in 16 genera, representing 109 different species, of which eight are new distributional records for the State of Amazonas. Furthermore, there are nine morphospecies which may represent undescribed new taxa, five of which are also new records for the State of Amazonas. Culex presented the highest number of species and the largest number of individuals. Anopheles, which represents 3% of the total sample, had the second highest number of species, followed by Wyeomyia. Psorophora and Aedes, represent the third and fourth largest number of individuals. The most abundant species was Cx. (Mel.) vaxus Dyar, 1920 followed by Cx. (Mel.) eknomios Forattini & Sallum, 1992, Cx. (Cux.) mollis Dyar & Knab, 1906, Cx. (Mel.) theobaldi Lutz, 1904, and Cx. (Cux.) declarator Dyar & Knab, 1906. The epidemiological and ecological implications of mosquito species found are discussed and are compared with other mosquito inventories from the Amazon region. The results presented represent the largest standardized inventory of mosquitoes of the Nhamundá and Abacaxis rivers, with the identification of 118 species level taxa distributed in seven localities, within four municipalities (Nhamundá, Maués, Borba, Nova Olinda do Norte), of which we have only few or no records in the published literature. © 2013 Sociedade Brasileira de Zoologia.